The Faraday Rotation Measure Grid of the LOFAR Two-metre Sky Survey: Data Release 2. Issue 4 (2nd January 2023) - O'Sullivan, S P; Shimwell, T W; Hardcastle, M J; Tasse, C; Heald, G; Carretti, E; Brüggen, M; Vacca, V; Sobey, C; Van Eck, C L; Horellou, C; Beck, R; et al.
ABSTRACT: A Faraday rotation measure (RM) catalogue, or RM Grid, is a valuable resource for the study of cosmic magnetism. Using the second data release (DR2) from the LOFAR Two-metre Sky Survey (LoTSS), we have produced a catalogue of 2461 extragalactic high-precision RM values across 5720 deg 2 of sky (corresponding to a polarized source areal number density of ∼0.43 deg −2 ). The linear polarization and RM properties were derived using RM synthesis from the Stokes Q and U channel images at an angular resolution of 20 arcsec across a frequency range of 120 to 168 MHz with a channel bandwidth of 97.6 kHz. The fraction of total intensity sources (>1 mJy beam −1 ) found to be polarized was ∼0.2 per cent. The median detection threshold was 0.6 mJy beam −1 (8σ QU ), with a median RM uncertainty of 0.06 rad m −2 (although a systematic uncertainty of up to 0.3 rad m −2 is possible, after the ionosphere RM correction). The median degree of polarization of the detected sources is 1.8 per cent, with a range of 0.05 per cent to 31 per cent. Comparisons with cm-wavelength RMs indicate minimal amounts of Faraday complexity in the LoTSS detections, making them ideal sources for RM Grid studies. Host galaxy identifications were obtained for 88 per cent of the sources, along with redshifts for 79 per cent (both photometric and spectroscopic), with the median redshift being 0.6. The focus of the current catalogue was on reliability rather than completeness, and we expect future versions of the LoTSS RM Grid to have a higher areal number density. In addition, 25 pulsars were identified, mainly through their high degrees of linear polarization.